2023
DOI: 10.18632/aging.204740
|View full text |Cite
|
Sign up to set email alerts
|

Xuebijing injection protects against sepsis-induced myocardial injury by regulating apoptosis and autophagy via mediation of PI3K/AKT/mTOR signaling pathway in rats

Abstract: Objective: Apoptosis and autophagy are significant factors of sepsis induced myocardial injury (SIMI). XBJ improves SIMI by PI3K/AKT/mTOR pathway. Present study is devised to explore the protective mechanism of XBJ in continuous treatment of SIMI caused by CLP. Methods: Rat survival was first recorded within 7 days. Rats were randomly assigned to three groups: Sham group, CLP group, and XBJ group. The animals in each group were divided into 12 h group, 1 d, 2 d, 3 d and 5 d according to the administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Inflammation and apoptosis are recognized as key pathophysiological phenomena in sepsis and SIMI at the cellular and molecular levels [7]. Many basic studies have indicated that regulate inflammation and apoptosis can reduce infectious cardiac insufficiency [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation and apoptosis are recognized as key pathophysiological phenomena in sepsis and SIMI at the cellular and molecular levels [7]. Many basic studies have indicated that regulate inflammation and apoptosis can reduce infectious cardiac insufficiency [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism by which sepsis-induced myocardial injury (SIMI) remains unclear [5,6]. Our previous studies have also demonstrated that autophagy and apoptosis play key roles in the occurrence and development of SIMI [7]. The PI3K/AKT/mTOR [8], MAPK [9] and NF-κB [10] and pathways regulate various biological responses, including proliferation, autophagy, inflammation, and apoptosis [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…XBJ ameliorates H2S-induced ARDS by promoting claudin-5 expression via the PI3K/AKT/Forkhead box protein O1 (FOXO1) signaling pathway [104] . XBJ produced a strong protective effect on sepsis-induced myocardial injury (SIMI) and may act by inhibiting apoptosis and promoting autophagy via , at least partially, activating PI3K/AKT/mTOR pathway in the early stage of sepsis, as well as promoting apoptosis and inhibiting autophagy via suppressing PI3K/AKT/mTOR pathway in the late stage of sepsis [105] . One of the main bioactive compounds is XBJ-benzoylpaeoniflorin (BPF).…”
Section: Potential Mechanisms Through Which Tmtfs Treat Covid-19mentioning
confidence: 99%
“…In the pathogenesis of sepsis, for instance, it has become clear that suppressing autophagy mechanisms by targeting SIRT4, MAPKs, and Nrf2 pathways may be a useful strategy for protecting organ function [177][178][179]. Indeed, it has also been demonstrated that autophagy is activated early in the onset of sepsis, but that as the condition progresses, autophagic activity declines [180,181]. There are opposing views in the existing literature on the crucial protective or destructive functions of autophagy in sepsis-induced organ damage.…”
Section: The Regulatory Role Of M 6 a Methylation Modified Autophagy ...mentioning
confidence: 99%